Multi-Sensory Factors When Examining Visual Fields in Unilateral Spatial Inattention and Its Effects on Treatment. - Smith Umbel, Tonya Marie; Baxstrom, Curtis R. (Optometry & Visual Performance, 2015)
Unilateral spatial inattention (USI) is sometimes challenging to differentiate from true hemianopsia. Visual field testing can appear to be variable and inconsistent. The results of field testing may be conflicting depending on the method used. Factors to consider are the presentation method of targets, dual presentation, differences in target size, and other variables demanding increased attention. It is also important to examine the multi-sensory influence on the performance of the patient based on the neural pathways being utilized in each task. The following is a discussion of evaluation techniques of visual fields in patients who have suffered an acquired brain injury. Further, there will be a case example of an individual diagnosed with a right middle cerebral artery stroke and secondary visual field defect who presented with unique visual field results. Knowledge gained from comparison of these procedures may affect treatment. For example, a patient may show no signs of USI while sitting but exhibit USI when asked to stand. This individual may demonstrate visual field difficulties when attending to anything involving movement and balance. This unique aspect of processing of vision from a multi-sensory model can make treatment for such individuals more efficient, well-defined, and effective. This information will be essential for multi-disciplinary interactions to create better treatment strategies among rehabilitation disciplines. The procedures to be evaluated will be confrontation fields, static automated perimetry, and tangent screen fields under varied circumstances and test conditions to optimize treatment and to maximize performance of daily living activities.